Pendampingan Pengolahan Minyak Kelapa dalam Mendukung Program Penguatan Profil Pelajar Pancasila di Sekolah Menengah - Rawung, Livana Dethris; Moko, Emma Mauren; Soputan, Grace Jenny; Rayer, Debby J J; Lihiang, Anatje; Wantania, Johanna Zusye (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The Pancasila Student Profile Strengthening Project or often referred to as the P5 Project is an effort to support the realization of student figures based on the Pancasila foundation through the process of reviewing student learning materials based on projects. One of the topics of the P5 activities carried out at SMA N 2 Ratahan is entrepreneurship, and coconut oil processing is the theme raised. The implementation method of community service activities consists of dissemination, training/technology transfer, as well as monitoring and evaluation at the final stage. Through this community service activity, there is an increase in the level of community empowerment in this case students and teachers, namely increasing student knowledge and skills about processing coconuts into coconut oil and blondo using more modern tools. The activities include production and packaging. This activity has also been able to improve students' life skills to be able to become entrepreneurs later.